The Role of Motivation as Mediation in The Influence of Career DEV and PS Cap on Perform (Study on Kayawan PT. Lotte Shopping Indonesia) - Yosia Riski David Santoso; Bambang Suko Priyono (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The research objective was to analyze and describe the influence of career development and psychological capital on employee performance mediated by the work motivation of the employees of PT. Lotte Shopping Indonesia. The population used in this study were employees of PT. Lotte Shopping Indonesia, amounting to 138 people. The sampling method in this study used a census. The data analysis technique used regression using the SPSS program and the Sobel test. The results of this study can be concluded that career development has a positive effect on work motivation. Psychological capital has a positive effect on work motivation. Career development has a positive effect on employee performance. Psychological capital has a positive effect on employee performance. Work motivation has a positive effect on employee performance. Work motivation is able to mediate the effect of career development on employee performance. Work motivation is able to mediate the effect of psychological capital on performance. Career development through work motivation is more effective in influencing employee performance than psychological capital.